2005
DOI: 10.1063/1.2031945
|View full text |Cite
|
Sign up to set email alerts
|

Combined electromagnetic and photoreaction modeling of CLD-1 photobleaching in polymer microring resonators

Abstract: By combining a solid-state photoreaction model with the modal solutions of an optical waveguide, we simulate the refractive index change due to the photobleaching of CLD-1 chromophores in an amorphous polycarbonate microring resonator. The simulation agrees well with experimental results. The photobleaching quantum efficiency of the CLD-1 chromophores is determined to be 0.65%. The combined modeling of the electromagnetic wave propagation and photoreaction precisely illustrates the spatial and temporal evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The variance of refractive index with depth z can be significant. 14 However, in the case of high light-intensity, this dependence is expected to be less. 41 Moreover, macroscopic quantities, such as effective index and hence coupling coefficient and resonant wavelength, would depend on the average value of refractive index, 42 averaged over the core layer thickness.…”
Section: Modeling Of Photobleaching-induced Refractive Index Changementioning
confidence: 99%
See 1 more Smart Citation
“…The variance of refractive index with depth z can be significant. 14 However, in the case of high light-intensity, this dependence is expected to be less. 41 Moreover, macroscopic quantities, such as effective index and hence coupling coefficient and resonant wavelength, would depend on the average value of refractive index, 42 averaged over the core layer thickness.…”
Section: Modeling Of Photobleaching-induced Refractive Index Changementioning
confidence: 99%
“…2,[9][10][11] With regard to photobleaching used for defining and/or trimming thin-film polymer waveguides, the interest goes further, into the domain of modeling the change in material refractive index as bleaching progresses. [12][13][14] We point out two limitations of the existing models. First, refractive index changes are calculated as a function of both waveguide depth and bleaching time.…”
Section: Introductionmentioning
confidence: 99%
“…There is not sufficient space to describe research on both all-organic and organic OEO/silicon photonic hybrid ring microresonators and the theory behind device design. The reader is referred to recent publications 9,[17][18][19][20][21][36][37][38][39][40][41][42][43][44][45][46] for a broader picture including to the fabrication of all-organic device structures by more novel techniques such as nanoimprint [17][18][19][20][21] and two-photon 42,44 lithography. Here we focus on presenting two different approaches to the fabrication of hybrid devices where the low dielectric breakdown threshold of silicon provides a challenge to induction of electro-optic activity by electric field poling.…”
Section: Fabrication Of Ring Microresonatorsmentioning
confidence: 99%
“…With lithium niobate, material loss is insignificant (∼ 0.2 dB/cm) and insertion loss is limited by index matching rather than mode size matching. A variety of novel device structures, including stripline, [31][32][33][34] cascaded prism, 35 all-organic ring microresonator, [17][18][19][36][37][38][39][40][41][42][43][44][45][46] and OEO/silicon photonic ring microresonator 20,21 structures have been fabricated from organic electro-optic materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that photobleaching leads to a reduced refractive index of polymer-dye composites [18,19], which results in a shift of the resonance positions to shorter wavelengths in WGM resonators. This effect has found applications in tuning the resonances of microring cavities doped with fluorescent dyes [20,21]. However, the influence of photobleaching on the performance of WGM laser biosensors remains to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%